USE OF GAMIFICATION FOR THE ACHIEVEMENT OF AN INTEGRATED BUSINESS MANAGEMENT (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The new millennium faced business management to new challenges as important as unpublished. The technological explosion, the neo-thinkers currents and the hyper competition have proposed unexplored ways to form and share the knowledge within the company in order to achieve its adaptation to the new time. One of these ways is to bring the game closer to the company, the practice conceptualized by anglicism "gamification". This buzzword integrates the group of emerging technologies on which the greater expectation of the international community falls, even when their contributions to success are just flourishing.The aim of this paper is to show how gamification can contribute to improve management, to achieve positive behavioral changes and to enhance economic results, provided that its implementation responds to a method that attends the pedagogical, motivational and technological aspects implied.
Keywords: gamification; game; serious game; method; management